Clinical Profile of Migrant Workers Admitted in Medical Ward at Tertiary Care Hospital - Ansari, Farmud; Yadav, Sushil; Ghimire, Ram Hari (Journal of Nobel Medical College, 2021)
Background: One of the defining elements of Nepal’s socioeconomic environment is labor migration. Migrant workers are more likely to develop occupational diseases because they do dangerous tasks and have limited access to occupational health care. The purpose of this paper is to produce clinical profile of migrant workers admitted in medical ward at tertiary care hospital. Materials and Methods: This was a descriptive cross-sectional study carried out in Nobel Medical College Teaching Hospital on migrant workers patients admitted in medical ward from October 2018 to September 2019. The sample enrollment process was consecutively who were admitted under medical ward. Pre-designed questionnaire was used to collect data for clinical profile of the patients. Data were entered in Microsoft Excel and analyzed. Results: The migrant workers in this study mainly came from Malaysia, United Arab Emirates, Saudi Arabia, Qatar and Kuwait. They are almost male (97.1%) in this study with mean age of 30.3±7 years in age. The commonest age group of migration was 20-29 year. The highest number of workers 22 (31.1%) had visited to Malaysia in the seek of work. The most common symptoms among them were weakness 15 (21.7%) and headache 13 (18.8%). The highest diagnosis among them was diabetes mellitus 13 (18.8%) and hypertension 11(15.9%). The highest number of workers was involved in their job at different foreign countries as a labor at factories or at construction site 32 (46.4%). Conclusion: Male from younger age group were mainly observed as migrant worker with their proclivity to work in Malaysia. The most common diagnosis among them was diabetes mellitus and hypertension. Most migrant workers worked as workers in factories and construction sites